Information and Communication Technologies in Tourism 2021 Proceedings of the ENTER 2021 eTourism Conference, January 19-22, 2021 - Wörndl, Wolfgang; Koo, Chulmo; Stienmetz, Jason L. (Springer International Publishing : Imprint: Springer, 2021)
This open access book is the proceedings of the International Federation for IT and Travel & Tourism (IFITT)'s 28th Annual International eTourism Conference, which assembles the latest research presented at the ENTER21@yourplace virtual conference January 19-22, 2021. This book advances the current knowledge base of information and communication technologies and tourism in the areas of social media and sharing economy, technology including AI-driven technologies, research related to destination management and innovations, COVID-19 repercussions, and others. Readers will find a wealth of state-of-the-art insights, ideas, and case studies on how information and communication technologies can be applied in travel and tourism as we encounter new opportunities and challenges in an unpredictable world.